Case Study: Analysis of Implementation of Inclusive Education at SDN Sumber Agung, Serang City - Aini, Syarifah; Az Zahra, Rizka; Apitasari, Pipit; Faradillah, Sarah; Rikmawati, Rikmawati (Peneliti.net, 2025)
This study aims to analyze the implementation of inclusive education at SDN Sumber Agung, Serang City, with a focus on the school's efforts to accommodate children with special needs (ABK) in a regular educational environment. The method used is qualitative research with a case study approach, which collects data through in-depth interviews, observations, and document analysis. The results of the study indicate that SDN Sumber Agung, Serang City has tried to implement inclusive education by adjusting the curriculum and teaching methods to meet the needs of ABK. The school also tries to create an environment that supports social interaction between regular and ABK students. However, several challenges are still faced, such as the limited number of teachers trained in inclusive education and facilities that are not yet fully adequate. These findings indicate the importance of improving teacher competence in dealing with ABK and providing facilities and infrastructure that are more in accordance with the needs of inclusive students. Therefore, it is recommended that schools work together with the government to provide routine training for educators and improve existing educational facilities. This study is expected to contribute to the development of inclusive education in elementary schools, especially in areas with similar challenges. Thus, inclusive education at SDN Sumber Agung, Serang City can be more effective in creating equal opportunities for all students to develop optimally.